Gerak Tari Baris Tunggal dalam Fotografi Ekspresi Menggunakan Teknik Strobo Light - Ida Bagus Candra Yana* (Rekam: Jurnal Fotografi, Televisi, Animasi)
Dance  photography  is  a  photo  shoot  on a  dance  movement  which  has  a  characteristic as  it  shows  on  a  particular  movement  with unique costumes. The arts of dance photography specifically describes through a specific thematic effect  with  an  aesthetic  and  creative  oncoming. Based on the photographer experience to capture the  light  together  with  his  aesthetic  expression on  movement  photography,  he  finally  presented the  visual  arts  on  Baris  Tunggal  Dance  in  art photography expressions using strobe light. Basically,  the  creative  works  focused on  the  dancer  movements  and  transformed  into photography  expression  which  blended  with aesthetic  and  creative  idea  (ideational)  also  the technical photo shoot capability (technical) of the photographer. The photo shoots technique chosen through a variety of consideration which oriented on practical implementations possibilities, resulting photographs  in  freeze,  blurred,  and  multiple-images  as  art  photography.  The  art  photograph includes  extrinsic  and  intrinsic  aesthetic  values through photo presentation. With the presence of this photography art works it was not only present Gerak Tari Baris Tunggal dalam Fotografi Ekspresi Menggunakan Teknik Strobo Light in the form of mere documentation but it was the art photography expression on creative and aesthetic level. Keywords:  movements,  Baris  Tunggal  Dance, photography expression, strobo-light * Dosen ISI Denpasar